2020
DOI: 10.1371/journal.pntd.0008119
|View full text |Cite
|
Sign up to set email alerts
|

S100A8/S100A9 deficiency increases neutrophil activation and protective immune responses against invading infective L3 larvae of the filarial nematode Litomosoides sigmodontis

Abstract: PLOS NEGLECTED TROPICAL DISEASESPLOS Neglected Tropical Diseases | https://doi.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 72 publications
(104 reference statements)
0
21
0
Order By: Relevance
“…For example, the increased parasite load in IL-6 and NOD2-deficient mice, which show a delayed neutrophil recruitment at the site of infection, is overcome by subcutaneous infection [ 47 , 49 ], resulting in a worm burden comparable to that of immunocompetent WT mice. However, mice deficient in S100A9 (which together with S100A8 forms a calprotectin that accounts for 40% of the cytosolic content of neutrophils) showed a similar decrease in parasite burden and an identical cell response in the pleural cavity, whether subcutaneously inoculated or naturally infected [ 50 ]. Also, at 8 days p.i., i.e.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the increased parasite load in IL-6 and NOD2-deficient mice, which show a delayed neutrophil recruitment at the site of infection, is overcome by subcutaneous infection [ 47 , 49 ], resulting in a worm burden comparable to that of immunocompetent WT mice. However, mice deficient in S100A9 (which together with S100A8 forms a calprotectin that accounts for 40% of the cytosolic content of neutrophils) showed a similar decrease in parasite burden and an identical cell response in the pleural cavity, whether subcutaneously inoculated or naturally infected [ 50 ]. Also, at 8 days p.i., i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Key results in immunological research include the discovery of a strong cross-reactivity between Onchocerca volvulus and L. sigmodontis antigen (Marcoullis and Gräsbeck 1976), the development of various vaccine protocols (primarily focused on attenuated L3 larvae with different adjuvants and treatment regiments) with varying degrees of success (reviewed in depth in Morris et al 2013), IgE dependent killing of MF by neutrophils and macrophages (Mehta et al 1980(Mehta et al , 1982, and the significance of IL-4, IL-4R, IL-5, and IL-17 for the containment of the infection (Le Martin et al 2000aMartin et al , 2000bVolkmann et al 2001Volkmann et al , 2003aTaylor et al 2006;Jenkins et al 2011;Ritter et al 2017Ritter et al , 2018aFrohberger et al 2019). Various studies have further shown that the protective immune responses against L. sigmodontis consist of both type 1 (Saeftel et al 2003;Muhsin et al 2018;Babayan et al 2003) and type 2 immune responses.…”
Section: Acanthocheilonema Viteae (Krepkogorskaja 1933)mentioning
confidence: 99%
“…With regard to granulocytes, eosinophils were shown to mediate protection via the major basic protein, eosinophil peroxidase, eotaxin-1 (Specht et al 2006;Gentil et al 2014), and eosinophil extracellular DNA traps (EETosis; Ehrens et al 2021), which contributes to MF and adult worm clearance (Martin et al 2000a). Neutrophils on the other hand are required for protective responses to invading infective L3 larvae and adult worms (Al-Qaoud et al 2000;Ajendra et al 2016;Frohberger et al 2020;Pionnier et al 2016). Studies on basophils during L. sigmodontis infection showed that basophil responses are suppressed during chronic infection, and basophils have no effect on the adult worm burden during primary infection (Larson et al 2012;Torrero et al 2010;Hartmann et al 2018).…”
Section: Acanthocheilonema Viteae (Krepkogorskaja 1933)mentioning
confidence: 99%
See 1 more Smart Citation
“…(associated with neutrophil recruitment [66]), and Retlnb (associated with worm death [48]), as well as ccl3 and cxcl5 (inflammatory chemokines) expression. Surprisingly, we found no differences between the trickle and bolus infections in any genes linked to Fc receptor signalling, despite the importance of antibody-mediated worm killing by macrophages and/or eosinophils within granulomas [14].…”
Section: In C56bl/6 Mice Granulomas From Bolus and Trickle-infected mentioning
confidence: 99%